Signet-Ring Cell Carcinoma as an Independent Prognostic Factor for Patients With Urinary Bladder Cancer: A Population-Based Study - Jin, Di; Qiu, Shi; Jin, Kun; Zhou, Xianghong; Cao, Qi; Yang, Lu; Wei, Qiang (Frontiers in Oncology, 2020)
Background: Primary signet-ring cell carcinoma (SRCC) is a rare variation of adenocarcinoma. Although SRCC of the urinary bladder is highly malignant, it is often neglected due to its rarity. Materials and methods: We used the national Surveillance, Epidemiology, and End Results (SEER) database (2004–2016) to compare SRCC with urothelial carcinoma (UC) and investigated the prognostic values of the clinicopathological characteristics and survival outcomes in SRCC of the urinary bladder. A multivariable Cox proportional hazard model, subgroup analyses, and propensity score matching (PSM) were used. Results: In all, 318 patients with SRCC and 57,444 patients with UC were enrolled. Compared with those with UC, patients with SRCC were younger at diagnosis (P < 0.001) and had higher rates of muscle invasive disease (P < 0.001), lymph node metastasis (P < 0.001), and distal metastasis (P < 0.001), as well as higher-grade tumors (P = 0.004). A Cox proportional hazard regression analysis showed that the SRCC group was associated with significantly higher risks of overall mortality (OM) compared with the UC group (hazard ratios (HR) = 1.44, 95% confidence intervals (95%CI) = 1.26–1.63, P < 0.0001). Patients with SRCC also had a higher risk of cancer-specific mortality (CSM; HR = 1.40, 95%CI = 1.18–1.65, P < 0.0001). After PSM, the SRCC group also experienced higher risks of OM (HR = 1.45, 95%CI = 1.24–1.68, P < 0.0001) and CSM (HR = 1.47, 95%CI = 1.20–1.79, P = 0.0001) compared with the UC group. In the subgroup analyses, no significant interactions were observed in sex, age, N stage, M stage, and lymph nodes removed in terms of both OM and CSM. Conclusion: The prognosis of SRCC is poorer than that of UC, even after adjustment for baseline demographic and clinicopathological characteristic as well as cancer treatment. SRCC is an independent prognostic factor for patients with urinary bladder cancer.